Vulnerabilities in cryptographic hash functions: A practical study of hash cracking techniques and security implications - Redžepagić, Jasmin; Regvart, Damir; Rudeš, Hrvoje; Petrunić, Robert (Edelweiss Applied Science and Technology, 2025)
This paper explores hash functions and their security challenges, which ensure data integrity and confidentiality in digital systems. With advancing computing power, particularly GPUs and distributed networks, hash functions face increasing threats from brute-force, dictionary, and rainbow table attacks. Tools like Hashcat, Cain & Abel, and John the Ripper were analyzed for their efficiency against MD5, SHA-1, and SHA-512. Results highlight vulnerabilities in standard algorithms, emphasizing the need for more robust hash functions, especially in high-security and resource-constrained environments.